2016
DOI: 10.1002/cmdc.201600039
|View full text |Cite
|
Sign up to set email alerts
|

The Cell Surface Receptor CD44: NMR‐Based Characterization of Putative Ligands

Abstract: The cell surface receptor CD44 is a glycoprotein belonging to the hyaluronan-binding proteins, termed hyaladherins. CD44 is expressed in a wide variety of isoforms in many cells, and in particular is present on the surface of malignant cells where it is involved in the onset and progression of cancer. In a first attempt to identify novel CD44 binding agents, we first characterized via nuclear magnetic resonance (NMR) techniques, several agents that were reported to bind to hCD44. To our surprise, however, none… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 54 publications
(105 reference statements)
1
9
0
Order By: Relevance
“…Besides that of heparin, the binding of OPN to hyaluronic acid (HA), another ubiquitous extracellular matrix glycosaminoglycan, , was tested (Figure S8). HA is composed of N -acetylglucosamine and glucuronic acid and binds to the abundant extracellular receptor CD44 through a conserved HA binding domain (CD44 HABD ). , OPN was also described as a binding partner of CD44 (with and without HA) . Given the polyanionic nature of HA and heparin, a similar mode of binding to OPN can be anticipated.…”
Section: Resultsmentioning
confidence: 99%
“…Besides that of heparin, the binding of OPN to hyaluronic acid (HA), another ubiquitous extracellular matrix glycosaminoglycan, , was tested (Figure S8). HA is composed of N -acetylglucosamine and glucuronic acid and binds to the abundant extracellular receptor CD44 through a conserved HA binding domain (CD44 HABD ). , OPN was also described as a binding partner of CD44 (with and without HA) . Given the polyanionic nature of HA and heparin, a similar mode of binding to OPN can be anticipated.…”
Section: Resultsmentioning
confidence: 99%
“…uPA-A6-CD44 + -ENaC cascade regulates the fate of AT2 cells in re-alveolarization (24). uPA possesses a A6 motif showing high affinity with CD44 receptors (33,34). Elevated PAI-1 may interrupt the uPA-CD44 receptor binding competitively.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have indicated that this peptide is a noncompetitive antagonist for the uPA‐uPAR complex, and some have shown that this peptide has homology with a part of CD44 (120‐NASAPPEE‐127) and introduced this protein as the A6 receptor 27,92 . In a structural biology study, 40 Baggio et al showed that the HA‐binding domain is probably part of CD44 that interacts with A6. But due to the use of a non‐glycosylated protein (this domain of CD44 has several glycosylated sites), they could not recognize the exact binding pocket of A6.…”
Section: Discussionmentioning
confidence: 99%